ПОГЛЯДИ ПЕДОЛОГІВ НА ПРИЧИНИ ПОЯВИ «МОРАЛЬНО ДЕФЕКТИВНИХ» ДІТЕЙ У ПУБЛІКАЦІЯХ В ПЕДАГОГІЧНИХ ЖУРНАЛАХ (20-30 рр. ХХ ст.) - Бондарець Марія (World Science, 2019)
In the article based on the analysis of publications in pedagogical journals of the 20-30s of the XX century (“The Way of Education”, “The Way of Enlightenment”, “Pedology”, “Our School”) the views of well-known psychologists and educationists on the social causes of the emergence of “morally defective children” have been generalized. It has been found that the term “morally defective child” was used to refer to children who suffered from character and emotional-will disorders, and who were prone to aggressive and unlawful behavior or were pedagogically neglected, homeless, etc. The ambiguity of approaches to the interpretation of the causes of the emergence of “morally defective” children in the pedagogy and psychology of the studied period has been proved. In particular, A. Zalkind, L. Vygotskyi, O. Mukhina, M. Tarasevich in their works substantiated the role of the social environment as a factor of morally defective childhood. It has been proved the interconnection of moral deficiency with the socio- economic and cultural-pedagogical conditions of the development and upbringing of a child.